Nilai Konservasi Tinggi Kawasan Hutan Nusakambangan Sebagai Sumber Penghidupan bagi Masyarakat Lokal - Eming Sudiana; Imam Widhiono MZ (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
A study on ecosystem services of Nusakambangan tropical low land rain forest was conducted by survey method. The purposes of this study are to identify the ecosystem services needed by local community families, to define degree of dependency of the local community family on the ecosystem services, to know the status of high conservation value (HCV 5) and to design the conservation strategy. The results showed that Nusakambangan low land rain forest has HCV 5. The basic need of the local community families has depends on the ecosystem service of Nusakambangan tropical low land rain forest. The silvopastory technology can be applied as conservation strategy of Nusakambangan tropical low land rain forest.